Evidentiality and propositional scope in early modern German - Whitt, Richard J. (John Benjamins, 2018)
This paper provides an overview of verbal markers of evidentiality in Early Modern German (1650-1800) in light of Boye’s propositional scope hypothesis. The markers under investigation include the semi-auxiliary scheinen ‘to shine, appear, seem’ and the perception verbs sehen ‘see’ and hören ‘hear.’ It is shown that, although Boye’s hypothesis sheds new light on and calls into question previous diachronic accounts of scheinen, it appears not to fully account for why cases where perception verbs do not scope over propositions are also found with evidential readings in light of the larger discourse context. It will be shown that Boye’s hypothesis is still feasible when such contexts are taken into account. Data are drawn from the German Manchester Corpus (GerManC), a representative multi-register corpus of Early Modern German from 1650 to 1800.